Stress and Burnout among Medical Specialists in Romania: A Comparative Study of Clinical and Surgical Physicians - Ioana Silistraru; Oana Olariu; Anamaria Ciubara; Ștefan Roșca; Anisia-Iuliana Alexa; Florentina Severin; Doina Azoicăi; Radu Dănilă; Sergiu Timofeiov; Ioan-Adrian Ciureanu (MDPI AG, 2024)
This study, which focuses on 227 participants (196 females and 31 males) comprising 187 clinical specialists and 40 surgical physicians, examines the prevalence of burnout in medical specialists. We investigate the effects of the emotional exhaustion (EE), Depersonalization (D), and personal accomplishment (PA) dimensions on professional satisfaction and plans to change careers using the modified licensed Maslach Burnout Inventory-Human Services Survey (MBI-HSS (MP)). High emotional exhaustion is reported by 52.63% of men and 71.28% of women in the clinical medicine group (n = 188). In the surgical specialties (n = 39), scores are significantly higher, with 75% of men and 77.77% of women reporting EE. In our sample group, 71.36% express high levels of emotional exhaustion, with similar patterns across specialization and gender. Clinical medicine respondents report high degrees of depersonalization in 33.13% of females and 21.05% of males, while surgical specialty respondents report high levels in 33.33% of females and 50% of males. Across genders and specializations, 33.03% of all respondents show high levels of depersonalization. Clinical medicine participants report high levels of personal accomplishment (42.60% of females and 42.10% of males), whereas surgical specialties report 44.44% of females and 66.66% of male on the PA dimension. Of the total number of respondents, 44.05% report having a high level of personal accomplishment; differences exist depending on specialty and gender. In addition, questions regarding professional fulfilment and intention to change careers were presented to the participants. A total of 53.40% (16 male and 105 female) of the clinical medicine respondents said they intended to change careers, while 33 participants (9 male, 34 female) doubted if they would remain in the same specialization. Furthermore, 86 individuals (9 male and 77 female) in the surgical specialties said they would never choose to work in healthcare again. Regression analysis suggests that being male, higher in age, and working in surgical specialties with lower job satisfaction and a higher intention to change profession are associated with higher levels of EE. Age and work satisfaction are significant predictors of depersonalization, and higher career satisfaction is associated with increased levels of PA.